2018
DOI: 10.1159/000487965
|View full text |Cite
|
Sign up to set email alerts
|

A Network-Wide Stroke Team Program Reduces Time to Treatment for Endovascular Stroke Therapy in a Regional Stroke-Network

Abstract: Background and Purpose: Driven by the positive results of randomized, controlled trials of endovascular stroke therapies (EVT) in stroke patients with large vessel occlusion, different approaches to speed up the workflow for EVT candidates are currently being implemented worldwide. We aimed to assess the effect of a simple stroke network-wide workflow improvement project, primarily focusing on i.v. thrombolysis, on process times for patients undergoing EVT. Methods: In 2015, we conducted a network-wide, peer-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
2
Order By: Relevance
“…We have previously applied the stroke team approach to the sponsor's stroke admissions team (16) and consequently to our regional stroke network (17), which at the time consisted of seven stroke units. In that study, we found that the intervention (algorithm design, introducing CRM, and simulation training) was effective in reducing the network wide door-to-needle time from a median of 43 min (IQR 30–60 min) to 31 min (IQR 24–42 min) (16) and door-to-groin-time from 59 min (IQR 35–102 min) to 43 min (IQR 28–81 min) (25). However, these studies were limited to a regional network consisting of heterogeneous stroke units of different sizes with and without the capacity for EVT.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously applied the stroke team approach to the sponsor's stroke admissions team (16) and consequently to our regional stroke network (17), which at the time consisted of seven stroke units. In that study, we found that the intervention (algorithm design, introducing CRM, and simulation training) was effective in reducing the network wide door-to-needle time from a median of 43 min (IQR 30–60 min) to 31 min (IQR 24–42 min) (16) and door-to-groin-time from 59 min (IQR 35–102 min) to 43 min (IQR 28–81 min) (25). However, these studies were limited to a regional network consisting of heterogeneous stroke units of different sizes with and without the capacity for EVT.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have concluded the benefits of physician education and feedback on improving in‐hospital procedural metrics and streamlining reperfusion therapy delivery, with a 2019 meta‐analysis concluding that physician feedback results in the greatest median reduction in treatment time (64 minutes, P = .002). Components of physician education have been incorporated into multiple trials, all of which have improved in‐hospital workflows 40,78‐80 . A 2015 network‐wide stroke improvement programme found stroke education, and regular simulation training was critical to improving median DPT by 15.5 minutes; however, this did not reach statistical significance 78 .…”
Section: In‐hospital Workflow Parametersmentioning
confidence: 99%
“…Components of physician education have been incorporated into multiple trials, all of which have improved in‐hospital workflows 40,78‐80 . A 2015 network‐wide stroke improvement programme found stroke education, and regular simulation training was critical to improving median DPT by 15.5 minutes; however, this did not reach statistical significance 78 . A 5‐year prospective database registry concluded that the use of stroke triage education, procedural standardization and temporal feedback systems achieved significant reductions in angiography‐to‐recanalization times by 69 minutes, with significant improvements in all aspects of angiography workflow and associated clinical outcomes 80 .…”
Section: In‐hospital Workflow Parametersmentioning
confidence: 99%
“…Our training sessions have significantly improved staff satisfaction, patient safety and stroke readiness 12. We applied this approach to our regional stroke network comprising seven stroke units, and found that the intervention (algorithm design, education about team communication and simulation training) as well as the implicit cultural changes reduced the network-wide door-to-needle11) time from a median of 43 min (IQR 30–60) to 31 min (IQR 24–42)12 and door-to-groin time by 16 min (from 59 min (IQR 35–102) to 43.3 min (IQR 28–81)) 11. We are currently conducting an interventional multicentre study in Germany to evaluate crew-resource management-based multipart intervention in acute stroke care (Simulation-based Training of Rapid Evaluation and Management for Acute Stroke trial, ClinicalTrials.gov Identifier: NCT03228251).…”
Section: Crew-resource Management Strategies and Special Tools For Acmentioning
confidence: 99%